Antagonistic Property of G2013 (α-L-Guluronic Acid) on Gene Expression of MyD88, Tollip, and NF-ΚB in HEK293 TLR2 and HEK293 TLR4 - Sharifi, Laleh; Aghamohammadi, Asghar; Aletaha, Somaye; Bigdeli, Razieh; Asgary, Vahid; Bokaie, Saied; Asgardoon, Mohammad H.; Azizi, Gholamreza; Mirshafiey, Abbas (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Introduction: Inhibition of Toll-like receptors (TLRs) signaling plays a crucial role in suppressing the inflammation and available data presenting G2013 as an immunomodulatory agent, therefore, we designed this study to answer whether G2013 can affect the signaling pathway of TLR2 and TLR4. Methods: Cytotoxicity study of G2013 was performed by MTT assay. HEK293 TLR2 and HEK293 TLR4 cell lines were cultured and treated with low dose (5μg/ml) and high dose (25μg/ml) of G2013 for 24 hours. Gene expressions of MyD88, Tollip, and NF-ΚB were defined by quantitative real-time PCR. Results: The cytotoxicity assay showed that the concentrations lesser than 125μg/ml of G3012 had no apparent cytotoxicity, however, the concentrations of 5μg/ml and 25μg/ml could suppress the mRNA expression of MyD88, Tollip and NF-ΚB in HEK293 TLR2 and HEK293 TLR4 cell lines. Conclusion: in our study, we verified the linkage between the immunosuppressive property of G2013 and TLR2, TLR4 signaling cascade; but so far, the specific target of G2013 and its molecular mechanism has not been detected yet. We recommend further studies on other Patten Recognition Receptors (PRRs)and other mechanisms of inflammation like oxidative stress to be conducted in the future.
Keywords: MyD88